An 11-year nationwide registry-linkage study of opioid maintenance treatment in pregnancy in Norway - Ingvild Odsbu; Milada Mahic; Svetlana Skurtveit; Ingunn-Olea Lund; Marte Handal (Norsk Forening for Epidemiologi, 2021)
Aim: We aimed to describe opioid maintenance treatment (OMT) to pregnant women in Norway and study the background characteristics of the pregnant women compared to the general population of pregnant women and to a previous clinical cohort study of OMT in pregnancy. Methods: Population-based cohort study with linked data from the Norwegian Medical Birth Registry, the Norwegian Prescription Database, the Norwegian Patient Registry, and Statistics Norway. The study population consisted of women giving birth between 2005-2015 in Norway. We defined OMT pregnancies as pregnancies where the woman was dispensed OMT medications (methadone, buprenorphine, or buprenorphine/ naloxone) at least once during pregnancy. Results: The study population consisted of 420,808 women with 645,440 pregnancies ending in a live birth in Norway in 2005-2015 (the general pregnant population). Of these, 261 women (0.6‰) had altogether 306 OMT pregnancies. The mean number of pregnancies was 28 OMT pregnancies per year and quite stable during the study period. Women with OMT pregnancies were older, smoked tobacco more frequently, had lower education, and fewer of them had a partner, compared to the general population of pregnant women. In most pregnancies, the women were treated with buprenorphine (n=183 (59.8%)), while in 120 (39.2%) pregnancies, the woman received methadone. From 2008, buprenorphine replaced methadone as the most frequently used drug. In only 38 (12.4%) pregnancies, OMT treatment was initiated in pregnancy. In 201 (66%) pregnancies, the woman used OMT medications in all trimesters. For these women, the mean amount of dispensed drug was 3.4 DDD/day (85 mg/day) in pregnancy for methadone and 1.9 DDD/day (15.2 mg/day) for buprenorphine. Conclusion: The number of OMT pregnancies per year has been low and stable in the period 2005-2015. Following Norwegian recommendations, there has been a shift from treatment with methadone towards buprenorphine. The women receiving OMT during pregnancy had more risk factors for adverse outcomes than the general pregnant population but were quite similar to the previous clinical cohort.